Terahertz spectroscopy and solid-state density functional theory calculations of cyanobenzaldehyde isomers - Dash, Jyotirmayee; Ray, Shaurnik; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin B.; Gonnade, Rajesh G.; Ambade, Ashootosh V.; Joshi, Kavita; Pesala, Bala (Journal of Physical Chemistry A, 2015)
Spectral signatures in the terahertz (THz) frequency region are mainly due to bulk vibrations of the molecules. These resonances are highly sensitive to the relative position of atoms in a molecule as well as the crystal packing arrangement. To understand the variation of THz resonances, THz spectra (2-10 THz) of three structural isomers: 2-, 3-, and 4-cyanobenzaldehyde have been studied. THz spectra obtained from Fourier transform infrared (FTIR) spectrometry of these isomers show that the resonances are distinctly different especially below 5 THz. For understanding the intermolecular interactions due to hydrogen bonds, four molecule cluster simulations of each of the isomers have been carried out using the B3LYP density functional with the 6-31G(d,p) basis set in Gaussian09 software and the compliance constants are obtained. However, to understand the exact reason behind the observed resonances, simulation of each isomer considering the full crystal structure is essential. The crystal structure of each isomer has been determined using X-ray diffraction (XRD) analysis for carrying out crystal structure simulations. Density functional theory (DFT) simulations using CRYSTAL14 software, utilizing the hybrid density functional B3LYP, have been carried out to understand the vibrational modes. The bond lengths and bond angles from the optimized structures are compared with the XRD results in terms of root-mean-square-deviation (RMSD) values. Very low RMSD values confirm the overall accuracy of the results. The simulations are able to predict most of the spectral features exhibited by the isomers. The results show that low frequency modes (<3 THz) are mediated through hydrogen bonds and are dominated by intermolecular vibrations.

Visible light-triggered disruption of micelles of an amphiphilic block copolymer with BODIPY at the junction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (Chemical Communications, 2015)
A visible light-cleavable polymer is synthesised to overcome the limitations of UV-sensitive polymers. Photocleavable BODIPY functionalized with an ATRP initiator and alkyne was used to obtain an amphiphilic block copolymer by conducting the click reaction and polymerization simultaneously. Micellar assembly of the polymer was disintegrated under visible light irradiation with controlled release of cargo.

Photoresponsive assemblies of linear-dendritic copolymers containing azobenzene in the dendron interior: the effect of the dendron structure on dye encapsulation and release - Kalva, Nagendra; Basutkar, Nitin B.; Ambade, Ashootosh V. (RSC Advances, 2016)
Hydrophobic dendrons with different numbers and positions of azobenzenes as well as different groups benzyl and dodecyl, on the periphery were synthesised and attached to poly(ethylene glycol) using copper-catalysed azide-alkyne cycloaddition to obtain linear-dendritic copolymers. Self-assembly of the polymers in aqueous solution was characterised using dynamic light scattering (DLS), transmission electron microscopy (TEM) and critical micelle concentration (cmc). Formation of H-aggregates during micellisation was shown for polymers with a higher number of azobenzene units. Photoisomerisation of azobenzene in the assemblies was studied and the rate constant of thermal photoisomerisation was calculated. Release of hydrophobic dye Nile red upon photoisomerisation of azobenzene occurred without disruption of micellar aggregates. Dye release varied with the pathway - thermal or visible light irradiation, followed for cis-trans isomerisation. The encapsulation capacity of the micelles and extent of dye release in either pathway were found to be influenced by the dendron structure. A polymer with a lower number of azobenzenes and aliphatic periphery on the dendron showed significantly different behaviour than polymers with a larger number of aromatic units.

Copper and silver nanoparticles stabilized by bistriazole-based dendritic amphiphile micelles for 4-nitrophenol reduction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (New Journal of Chemistry, 2017)
Copper and silver nanoparticles were fabricated in aqueous solution using micellar assemblies of dendritic amphiphiles containing triazole rings. Dendritic amphiphiles displaying a bistriazole unit between a hydrophobic benzyl ether dendron and two oligo(ethylene glycol) (OEG) chains were synthesized using click chemistry. Micelles were characterized by DLS, TEM, CMC determination, and dye encapsulation. Micellar size was dependent on the dendron backbone structure and OEG chain length. Metal nanoparticles were characterized by TEM and UV-Vis spectroscopy. The Cu NPs had a smaller average particle diameter than the Ag NPs. The micelle-stabilized nanoparticles, at a concentration of 7.5 ppm, were shown to efficiently catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 in aqueous solution without stirring, using up to 1 ppm of substrate. The reaction catalyzed by Cu NPs followed zero order kinetics (k = 3.48 x 10(-3) M s(-1)), while the Ag NP-catalyzed reaction followed pseudo-first order kinetics (k = 1.28 x 10(-3) s(-1)).

Visible light and pH-responsive star copolymer and doxorubicin-polymer conjugate micelles for combination drug delivery and bioimaging - Basutkar, Nitin B.; Surapaneni, Sai Geetika; Alam, Md. Shafi; Ambade, Ashootosh V. (Journal of macromolecular science part A- pure and applied chemistry, 2024)
Amphiphilic 3-arm star copolymer containing visible light-cleavable BODIPY group and pH-responsive imine bonds at the junction of hydrophilic poly(ethylene glycol) (PEG) and two poly(epsilon-caprolactone) (PCL) arms was synthesized by the combination of ring-opening polymerization (ROP) and click chemistry. The formation and stimuli-responsive disruption of micelles were analyzed using dynamic light scattering and transmission electron microscopy. Dual stimuli-responsive release of anticancer drugs Doxorubicin (Dox) and Camptothecin (CPT) from the micelles was studied. Micellar assemblies containing Dox conjugated to PEG-BODIPY through imine bonds were prepared and controlled release of Dox in response to visible light and pH was shown. CPT and Dox-loaded star copolymer micelles as well as CPT loaded Dox-conjugated micelles were used in cellular uptake studies on MDA-MB 231 cells, and the synergistic effect of the two stimuli on the release of the two drugs was demonstrated inside the cells. Micellar assemblies also showed excellent bioimaging properties in the cellular uptake studies. [GRAPHICS]
Keywords: BODIPY; drug conjugate; micelles; pH-responsive; visible light-responsive